Farmers Perception towards Agri-clinical Services for Rubber Plantation Crop at Sepahijala District of Tripura - Mehta, Piyush; Debbarma, Chayan Mani; Raina, Krishan Kumar; Kashyap, Neha (International Journal of Economic Plants, 2020)
This study aims to access and evaluate the Farmers perception towards Agri-clinical services of the rubber crop. The study has taken readings on the basis of their awareness level towards clinical services, the perception regarding clinical services, the significance of issues during the application of clinical services and some suggestive opinions of farmers located at Sepahijala district of Tripura. Study has highlighted the level of awareness and knowledge among farmers for clinical services to be used for rubber plantation crop. The study has highlighted that the subsidies will increase more development in their purchasing capacity like equipment and tools and also it will lead to more participation in rubber farming. It has been categorically identified the core significance of clinical services among the key stakeholders of the plantation crop. Paper has made an attempt to find out the utilization of farm utility, schemes, proper handling of inputs and risk management functions of commodity.